Ethical considerations in global surgery: a scoping review - Grant, Chantalle Lauren (BMJ Glob Health, 2020)
INTRODUCTION: An unmet burden of surgical disease exists worldwide and is disproportionately shouldered by low-income and middle-income countries (LMICs). As the field of global surgery grows to meet this need, ethical considerations need to be addressed. Currently, there are no formal guidelines to help inform relevant stakeholders of the ethical challenges and considerations facing global surgical collaborations. The aim of this scoping review is to synthesise the existing literature on ethics in global surgery and identify gaps in the current knowledge. METHODS: A scoping review of relevant databases to identify the literature pertaining to ethics in global surgery was performed. Eligible articles addressed at least one ethical consideration in global surgery. A grounded theory approach to content analysis was used to identify themes in the included literature and guide the identification of gaps in existing literature. RESULTS: Four major ethical domains were identified in the literature: clinical care and delivery; education and exchange of trainees; research, monitoring and evaluation; and engagement in collaborations and partnerships. The majority of published literature related to issues of clinical care and delivery of the individual patient. Most of the published literature was published exclusively by authors in high-income countries (HICs) (80%), and the majority of articles were in the form of editorials or commentaries (69.1%). Only 12.7% of articles published were original research studies. CONCLUSION: The literature on ethics in global surgery remains sparse, with most publications coming from HICs, and focusing on clinical care and short-term surgical missions. Given that LMICs are frequently the recipients of global surgical initiatives, the relative absence of literature from their perspective needs to be addressed. Furthermore, there is a need for more literature focusing on the ethics surrounding sustainable collaborations and partnerships.